2020
DOI: 10.1097/mph.0000000000001998
|View full text |Cite
|
Sign up to set email alerts
|

Stuttering Priapism in a Teenage Boy: Lesson to be Learnt

Abstract: Untreated priapism can lead to ischemic damage of the penis and impotence. This case report describes a 14-year-old boy who presented with a history of priapism for 2 months, which was undiagnosed, ridiculed, and ignored even by medical practitioners. The underlying etiology was later identified to be chronic myeloid leukemia. Despite the usage of multimodal treatment, it took 7 days for control of priapism. The young boy is now left with an erectile dysfunction. The case highlights that priapism in children i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Of the combined treatment modalities, primary urological treatment and later introducing oncological treatment is most often described [3, 2941, 43, 4547, 44, 42, 48] [14, 51]. All patients received penile aspiration except three.…”
Section: Resultsmentioning
confidence: 99%
“…Of the combined treatment modalities, primary urological treatment and later introducing oncological treatment is most often described [3, 2941, 43, 4547, 44, 42, 48] [14, 51]. All patients received penile aspiration except three.…”
Section: Resultsmentioning
confidence: 99%
“…As age and experience increase, intention to purchase will increase. This contention is supported by Lodhi (2006) and Sachdeva, Bhatia and Kalra (2013). Ramasamy and Yeung (2003) added gender and marital status together with age and education.…”
Section: Background Of Studymentioning
confidence: 87%
“…Prathap and Rajamohan (2013) found that most investors had high-level awareness and positive approach towards investing in mutual funds. Similarly, the study by Sachdeva et al (2013) provided empirical evidence linking the risk perception of investors, which depended on age, experience, income and educational qualification, with their investing patterns or selections of particular brokers for their investments. In essence, risk perception was about the delicate balance and synergistic interactions among risk mapping, liquidity component, people and organisation to gain and sustain competitiveness in a highly volatile environment.…”
Section: Background Of Studymentioning
confidence: 99%
“…Despite the high white cell count in children at diagnosis, rheological problems are observed in less than 10% of children presenting with an extremely high median WBC of 458,000/µL [83]. Carefully history taking and physical examination is required in children admitted with CML because aside from typical symptoms of leukostasis like dyspnea, headache and dissziness, also blurred vision due to retinal bleeding and infiltrates with leukemic cells (Figure 4) (generally reversible within months) [84] can be observed, as well as low flow/venoocclusive priapism in boys (caveat: emergency scenario to avoid irreversible erectile dysfunction) [85][86][87], or hearing impairment (highly probably irreversible) [88]. Precautions to avoid tumor lysis syndrome include initial administration of fluid (dose 2 L/sqm body surface).…”
Section: Rheological Problems Associated With High White Cell and Plamentioning
confidence: 99%